The Impact of Brain-Based Teaching on Iranian EFL Learners' Vocabulary Retention and Recall - Davoud Amini; Mahsa Rahmani Asl; Abolfazl Ghasemzadeh (Journal of Modern Research in English Language Studies)
The brain-based learning (BBL) approach refers to a learning method which attends to the structural and functional properties of the brain when involved in learning. The proponents of BBL approach in language teaching have proposed a set of strategies in line with neuroscientific findings regarding the qualities of optimal language learning. Numerous studies have attested to effectiveness of these neuroeducational techniques. The present study attempted to investigate the effect of brainbased vocabulary teaching activities on EFL learners’ vocabulary retention and recall. The participants were 60 high school students in the Iranian EFL context selected via convenience sampling. The experimental group received 14 sessions of instruction in accordance with the BBL strategies suggested by Caine and Caine (1994). The findings revealed that the brain-compatible approach to teaching L2 vocabulary improved learners’ vocabulary retention. However, the intervention failed to have a significant effect on vocabulary recall. The divergent finding regarding the recall and retention of vocabulary is attributed to the intrinsic nature of productive vocabulary in developing in the long run as a result of deep emotional and cognitive engagement. The data collected with the perception questionnaire revealed that the majority of the participants demonstrated positive attitudes toward BBL strategies. Neuroeducational strategies facilitate vocabulary learning as a result of involving learners in deep emotional and cognitive engagement. Therefore, they should make up an integral aspect of foreign language teacher education programs. It is suggested that the synergic effects of the composure of BBL strategies for L2 teaching be investigated in relation to individual differences.